Spatially heterogeneous controls of soil organic carbon in a karst mountainous area of southern China: Insights from interpretable machine learning - Haofan Xu; Nannan Zhang; Manxuan Mao; Yunfan Li; Xiang Wang; Peter Croot; Weijun Fu; Xiaolin Sun; Shaowen Xie; Shujuan Liu; Hongyi Zhou; Chaosheng Zhang (Applied Geochemistry, 2026)

The influence of plantation forest legacy on blanket bog hydrology - Muhammad Jehanzaib; Raymond Flynn; Vicky Preece; Hannah Lehnhart-Barnett; Devin F. Smith; Oisín Leonard; Tiernan Henry; W. Berry Lyons; Anne E. Carey; Peter Croot (Journal of Hydrology, 2026)

Investigation of spatially varying relationships between cadmium accumulation and potential controlling factors in the topsoil of island of Ireland based on spatial machine learning approaches - Haofan Xu; Hailong Wang; Peter Croot; Juan Liu; Yunfan Li; Jingzi Beiyuan; Cheng Li; Bhupinder Pal Singh; Shaowen Xie; Hongyi Zhou; Chaosheng Zhang (Environmental Research, 2025)

Identification of the pollution sources and hidden clustering patterns for potentially toxic elements in typical peri-urban agricultural soils in southern China - Haofan Xu; Peng Hu; Hailong Wang; Peter Croot; Zhiwen Li; Cheng Li; Shaowen Xie; Hongyi Zhou; Chaosheng Zhang (Environmental Pollution, 2025)

All Aboard! Providing Shipboard Technical Skills While Building Capacity in Ocean Observations - Lilian Krug; Fiona Beckman; Andrew Rees; Angelika Dummermuth; Cassandre Stymiest; Eva-Maria Brodte; Karen Wiltshire; Peter Croot; Sophie Seeyave (Oceanography, 2025)
Shipboard training equips early career ocean professionals (ECOPs) with the skills, knowledge, and confidence to tackle the challenges of marine research. Such training helps develop a workforce essential for implementing a truly global ocean observation system and advancing understanding of the ocean and its sustainable use. Working with other organizations and individuals, the Partnership for Observation of the Global Ocean (POGO) offers opportunities to ECOPs, mainly from developing countries, to join research cruises and acquire hands-on experience with real-world oceanographic work. These learning experiences can be organized either as one-on-one training on research cruises with spare berths or collective training on dedicated expeditions designed for larger groups of international students. This article introduces POGO’s shipboard training program by presenting examples from each of the modalities, and it explores the program’s long-term impacts and future directions.

Identification of possible sources for potentially toxic elements and polycyclic aromatic hydrocarbons and their spatially varying relationships in urban soils of Dublin, Ireland - Haofan Xu; Hailong Wang; Bhupinder Pal Singh; Peter Croot; Chaosheng Zhang (Environmental Pollution, 2023)

Using the Red Band Difference Algorithm to Detect and Monitor a Karenia spp. Bloom Off the South Coast of Ireland, June 2019 - Catherine Jordan; Caroline Cusack; Michelle C. Tomlinson; Andrew Meredith; Ryan McGeady; Rafael Salas; Clynton Gregory; Peter L. Croot (Frontiers in Marine Science, 2021)
During the months of May, June, July and August 2019 the Red Band Difference algorithm was tested over Irish waters to assess its suitability for the Irish harmful algal bloom alert system. Over the 4 weeks of June an extensive localised surface phytoplankton bloom formed in the Celtic Sea, south of Ireland. Satellite imagery from the Sentinel-3a’s Ocean and Land Colour Instrument, processed using the Red Band Difference algorithm detected the bloom in surface shelf waters and helped monitor its movement. Daily satellite images indicated that the bloom appeared at the sea surface on the 2nd June 2019 and peaked in size and surface abundance in offshore shelf waters within 4 weeks, remnants remained at the surface into July. A particle tracking approach was used to replicate oceanic circulation patterns in the vicinity of the observed algal bloom and estimate its trajectory. The initial horizontal distribution of particles in the tracking model were based on a satellite imagery polygon of the bloom when it first appeared in surface waters. Good agreement was observed between satellite imagery of the bloom and the particle tracking model. In situ sampling efforts from a research cruise and the national inshore phytoplankton monitoring programme confirmed that Karenia mikimotoi was the causative organism of the bloom. This pilot study shows great potential to use the Red Band Difference algorithm in the existing Irish harmful algal bloom alert system. In addition, satellite ocean colour data combined with particle tracking model estimates can be a useful tool to monitor high biomass harmful algal bloom forming species, such as Karenia mikimotoi , in surface coastal waters around Ireland and elsewhere.

A First Global Oceanic Compilation of Observational Dissolved Aluminum Data With Regional Statistical Data Treatment - Jan-Lukas Menzel Barraqueta; Saumik Samanta; Eric P. Achterberg; Andrew R. Bowie; Peter Croot; Ryan Cloete; Tara De Jongh; Maria D. Gelado-Caballero; Jessica K. Klar; Rob Middag; Jean C. Loock; Tomas A. Remenyi; et al. (Frontiers in Marine Science, 2020)

Tracing sources of natural organic matter, trihalomethanes and metals in groundwater from a karst region - Connie O’Driscoll; Eoin McGillicuddy; Peter Croot; Pamela Bartley; John McMyler; Jerome Sheahan; Liam Morrison (Environmental Science and Pollution Research, 2020)

Corrigendum: Frequency of Microplastics in Mesopelagic Fishes from the Northwest Atlantic - Alina M. Wieczorek; Liam Morrison; Peter L. Croot; A. Louise Allcock; Eoin MacLoughlin; Olivier Savard; Hannah Brownlow; Thomas K. Doyle (Frontiers in Marine Science, 2018)

Frequency of Microplastics in Mesopelagic Fishes from the Northwest Atlantic - Alina M. Wieczorek; Liam Morrison; Peter L. Croot; A. Louise Allcock; Eoin MacLoughlin; Olivier Savard; Hannah Brownlow; Thomas K. Doyle (Frontiers in Marine Science, 2018)

Identifying the Sources and Sinks of CDOM/FDOM across the Mauritanian Shelf and Their Potential Role in the Decomposition of Superoxide (O2-) - Maija I. Heller; Kathrin Wuttig; Peter L. Croot (Frontiers in Marine Science, 2016)

Dissolved cadmium in the Southern Ocean: Distribution, speciation, and relation to phosphate - Oliver Baars; Wafa Abouchami; Stephen J. G. Galer; Marie Boye; Peter L. Croot (Limnology and Oceanography, 2014)
We report isotope dilution analyses of dissolved cadmium (Cd) and electrochemical Cd speciation measurements in the Atlantic sector of the Southern Ocean. Bioavailable inorganic Cd is > 100 times higher in near‐surface waters south of the Polar Front compared to the Subantarctic Zone because of upwelling and reduced complexation by organic Cd ligands. To trace local changes in the relation between Cd and P, we examine the deviations from a linear deep‐water Cd vs. P relation (Cd*), and find that changes in Cd* coincide with the position of frontal systems and covary with primary productivity and total dissolved Mn and Fe concentrations. These covariations agree with potential local changes in phytoplankton Cd uptake rates, resulting from differences in the availability of Cd, Zn, Mn, and Fe. A band of negative Cd* values is associated with formation of Subantarctic Mode Water (SAMW) and Antarctic Intermediate Water (AAIW). In contrast to SAMW, which may export low Cd : P ratios from the Southern Ocean, the Cd : P ratios in AAIW increase by mixing with underlying Upper Circumpolar Deep Water before being exported from the Southern Ocean. Deep waters show constant Cd : P ratios, and both elements behave conservatively with end‐member mixing between deep waters of the Weddell Gyre, the Antarctic Circumpolar Current, and inflowing North Atlantic Deep Water. Overall, our results support the hypothesis that the kink in the global Cd vs. P relation is largely caused by high Cd : P uptake ratios in the trace‐nutrient—limited Southern Ocean.

Solubility of iron in the Southern Ocean - Christian Schlosser; Christina L. De La Rocha; Peter Streu; Peter L. Croot (Limnology and Oceanography, 2012)
Iron solubility (cFe S ) ranged from 0.4 to 1.5 nmol L −1 , decreasing from south to north in three different Southern Ocean zones (the Coastal Zone, the Antarctic Zone, and the Polar Frontal Zone plus the Subantarctic Zone). This decrease was at times correlated with an increase in temperature. Organic Fe solubility (cFe S,org ), which was obtained by subtracting from total measured Fe solubility the solubility of inorganic species of iron (Fe) at the measurement temperature (20°C), ranged from 0.3 to 1.3 nmol L −1 , representing an average of 32 ± 14% of the concentration of ligands in the dissolved size fraction as determined via competitive ligand exchange‐absorptive cathodic stripping voltammetry (barring a handful of extremely high values from a transect run to the east of Prydz Bay). Values of cFe S were mainly lower than the predicted value for inorganic Fe solubility at the in situ temperature. Total in situ Fe solubility (cFe S,adj ) was therefore estimated by adjusting for inorganic Fe solubility at in situ temperatures (between −2°C and +18°C). Because in situ temperatures in the Antarctic Circumpolar Current were mostly lower than +3°C, such cFe S,adj values, ranging from 0.5 to 1.8 nmol L −1 , were roughly twice as large as cFe S,org . The adjustment relies heavily on model calculations of inorganic Fe solubility but, if correct, indicates that the bulk of the solubility of Fe in the cold waters of the Southern Ocean is tied to the solubility of inorganic Fe rather than to Fe ligands in the soluble size fraction.

Influence of river discharge in the tropical and subtropical North Atlantic Ocean - Leticia Cotrim da Cunha; Peter Croot; Julie LaRoche (Limnology and Oceanography, 2009)

Influence of temperature and salinity on the trace element incorporation into statoliths of the common cuttlefish (Sepia officinalis) - Karsten Zumholz; Thor H. Hansteen; Uwe Piatkowski; Peter L. Croot (Marine Biology, 2007)

Seasonal cycle of copper speciation in Gullmar Fjord, Sweden - Peter L. Croot (Limnology and Oceanography, 2003)
The chemical speciation of dissolved Cu was investigated by voltammetric methods in Gullmar Fjord, Sweden, over the course of a year from September 1996 until August 1997. Sampling was carried out on a roughly monthly basis, with an intensive survey carried out in May 1997. Surface water temperatures ranged from 21 to 22°C, whereas bottom waters in the fjord were approximately 6°C throughout. Macronutrient concentrations in the fjord during the period of the survey were investigated independently by the Göteborgs och Bohus lä4ns Vattenvårdsförbund (Water Quality Association of Göteborg and Bohus). Surface phosphate concentrations were highest in early spring with low levels ( ‐1 ) over the late spring and summer. Nitrate and silicate showed a similar pattern to phosphate with the exception of high concentrations encountered in surface waters when low salinity plumes caused by runoff were encountered. A period of calm, sunny weather in January 1997 saw the initiation of the spring bloom some 2 months earlier than usual. Dissolved Cu speciation was dominated by organic complexation (over 99.8%) throughout this study. Strong Cu binding ligands (log K > 12.5) were not detected during the winter or early spring and could be related to the temperature‐related seasonal appearance of the cyanobacterium Synechoccocus in these waters. The appearance of the strong Cu ligands led to a decrease in the concentration of free copper, resulting in a seasonal cycle for free copper in the fjord. This is the first study to examine Cu speciation over an annual cycle in a coastal environment.

Uptake and efflux of 64 Cu by the marine cyanobacterium Synechococcus (WH7803) - Peter L. Croot; Karlson Bengt; J. T. van Elteren; J. J. Kroon (Limnology and Oceanography, 2003)
The uptake and efflux of 64 Cu was studied in the marine cyanobacterium Synechoccous strain WH7803 (DC2). Uptake followed classical Michaelis∐Menten type kinetics in metal∐buffered seawater. The maximum uptake rate, V max , was 0.236 ± 0.016 × 10 −18 mol Cu cell −1 h −1 , with the half∐saturation constant, K S , of 10 −10.81±0.11 mol L −1 . An efflux mechanism was also observed in WH7803, whose growth was inhibited by high internal Cu concentrations. Efflux of Cu enabled WH7803 to maintain homeostasis for Cu at typical seawater ambient free copper concentrations ([Cu 𠀫 ] f ). The sensitivity of WH7803 growth to Cu was related to a simple inability to regulate internal Cu concentrations when external concentrations were >10 −11 mol L −1 .

Iron uptake and physiological response of phytoplankton during a mesoscale Southern Ocean iron enrichment - Maria T. Maldonado; Philip W. Boyd; Julie LaRoche; Robert Strzepek; Anya Waite; Andrew R. Bowie; Peter L. Croot; Russell D. Frew; Neil M Price (Limnology and Oceanography, 2001)
Iron supply is thought to regulate primary production in high nitrate, low chlorophyll (HNLC) regions of the sea in both the past and the present. A critical aspect of this relationship is acquisition of iron (Fe) by phytoplankton, which occurs through a complex series of extracellular reactions that are influenced by Fe chemistry and speciation. During the first in situ mesoscale Fe‐enrichment experiment in the Southern Ocean (Southern Ocean iron release experiment [SOIREE]), we monitored the uptake of Fe by three size classes of plankton and their ensuing physiological response to the Fe enrichment. Rates of Fe uptake from both inorganic Fe (Fe′) and organic Fe complexes (FeL) were initially fast, indicative of Fe‐limitation. After Fe enrichment phytoplankton down‐regulated Fe uptake and optimized physiological performance, but by day 12 they had greatly increased their capacity to acquire Fe from FeL. The increase in Fe uptake from FeL coincided with a sixfold decrease in Fe′ that followed the production of Fe‐binding organic ligands. Phytoplankton were able to use organically bound Fe at rates sufficient to maintain net growth for more than 42 d. Adaptation to such shifts in Fe chemistry may contribute to bloom longevity in these polar HNLC waters.

Growth rates of large and small Southern Ocean diatoms in relation to availability o iron in natural seawater - Klaas R. Timmermans; Loes J. A. Gerringa; Hein J. W. de Baar; Bas van der Wagt; Marcel J. W. Veldhuis; Jeroen T. M. de Jong; Peter L. Croot; Marie Boye (Limnology and Oceanography, 2001)
Blooms of large diatoms dominate the CO 2 drawdown and silicon cycle of the Southern Ocean in both the past and present. The growth of these Antarctic diatoms is limited by availability of iron (and light). Here we report the first assessment of growth rates in relation to iron availability of two truly oceanic Antarctic diatom species, the large, chain‐forming diatom Chaetoceros dichaeta and the small, unicellular diatom C. brevis . In Filtered natural, untreated Southern Ocean water, a maximum specific growth rate of 0.62 ± 0.09 d −1 and a Km for growth of 1.12 x 10 9 M dissolved iron was calculated for C. dichaeta . This response could only be seen during a long‐day light period. C. brevis maintained growth rates of 0.39 ± 0.09 d −1 with and without iron addition, even under short‐day light conditions, and could only be forced into iron limitation by adding the siderophore desferri‐ferrioxamine B (DFB), an iron immobilizing agent. Using this approach, the low Km value for growth of 0.59 × 10 −12 M dissolved Fe was calculated for this species. The size‐class dependent growth response to iron (and light) confirms the key role of these parameters in structuring Southern Ocean ecosystems and thus the CO 2 dynamics and the silicon cycle.

Production of extracellular Cu complexing ligands by eucaryotic phytoplankton in response to Cu stress - Peter L. Croot; James W. Moffett; Larry E. Brand (Limnology and Oceanography, 2000)
Organic chelators that are thought to be of recent biological origin control copper speciation in seawater. Previous studies have often resolved these copper binding ligands into two classes, class 1 ligands (conditional stability constants 10 12 –10 14 M −1 ) and class 2 ligands (conditional stability constants 10 9 –10 12 M −1 ). At present the sources and structures of these chelators are unknown. Previous work has shown that in response to copper toxicity, cultures of the marine cyanobacteria Synechococcus spp. produce a strong ligand, similar in binding strength to class 1 ligands. We extended this work by surveying a suite of copper‐stressed marine eucaryotic phytoplankton for the production of copper binding ligands. Most eucaryotic species we studied did not produce ligands with the binding strength of class 1 ligands, but many produced class 2 ligands. A marine dinoflagellate Amphidinium carterae was found to produce very strong ligands; however, the low abundance of dinoflagellates in the open ocean may mean that this source of class 1 ligands is more important in coastal waters. This survey shows that there are many biological sources of copper binding ligands, but that procaryotes such as cyanobacteria are more plausible sources of class 1 ligands in the open ocean than eucaryotes.

Cu speciation and cyanobacterial distribution in harbors subject to anthropogenic Cu inputs - James W. Moffett; Larry E. Brand; Peter L. Croot; Katherine A. Barbeau (Limnology and Oceanography, 1997)
Cu speciation was studied in four harbors on the south coast of Cape Cod, Massachusetts, that are exposed to varying degrees of Cu contamination from anthropogenic sources. Copper in waters outside the harbors was complexed by ∼10 nM of very strong chelators, twofold higher than ambient Cu concentrations. In Eel Pond (Woods Hole) and Falmouth Inner Harbor, total dissolved Cu concentrations were 7–10‐fold higher. However, because the strong chelators were saturated in these two harbors, the free Cu increased by 1,000‐fold, from ∼10 −13 M to ∼10 −10 M. There was no evidence for any enhanced biological production of chelators in response to the elevated Cu concentrations. However, cell densities of cyanobacteria, which have been proposed as a source of strong Cu chelators in seawater, decline drastically in the high Cu harbors. These trends are consistent with culture studies showing that Synechococcus sp., the predominant cyanophyte in these waters, shows a dramatic decrease in growth rates above a free Cu 2+ level of 10 −11 M. In Great Pond and Waquoit Bay, which showed no significant Cu contamination or saturation of strong ligands, cyanobacterial cell densities showed little or no decrease. Results suggest that significant anthropogenic inputs of Cu may overwhelm processes occurring in seawater that lead Cu and strong chelator concentrations to approach comparable levels.